Exogenous Application of Glycine Betaine Maintains Bioactive Compounds, Antioxidant Activity, and Physicochemical Attributes of Blood Orange Fruit During Prolonged Cold Storage - Habibi, Fariborz; Valero, Daniel; Serrano, María; Guillén, Fabián (Frontiers in Nutrition, 2022)
Exogenous application of glycine betaine (GB) was evaluated on bioactive compounds, antioxidant activity, and physicochemical attributes of blood orange fruit cv. Moro stored at 3 ºC for 90 days. Vacuum infiltration (30 kPa) of GB was applied at 15 and 30 mM for 8 min. Parameters were measured after 1, 30, 60, and 90 days of storage plus 2 days at 20 °C to simulate the shelf-life (SL) period. GB treatments significantly reduced weight and ﬁrmness losses in ‘Moro’ blood orange fruit during cold storage. GB treatment maintained the higher concentration of organic acids (citric, malic, succinic, and oxalic acids) and sugars (sucrose, glucose, and fructose), especially for the higher GB doses (30 mM). During storage, GB treatments enhanced total anthocyanin concentration (TAC), total phenolic content (TPC), and total antioxidant activity (TAA). With respect to enzyme activities, the application of exogenous GB showed increases in catalase (CAT), ascorbate peroxidase (APX), superoxide dismutase (SOD), phenylalanine ammonia-lyase (PAL), while suppressed the polyphenol oxidase (PPO) activity. Overall, the most effective treatment was 30 mM GB leading to maintaining bioactive compounds, antioxidant activity, and quality in ‘Moro’ blood orange fruit during long-term storage. The positive results would permit the use of GB as a postharvest tool to maintain the quality attributes of blood orange fruit.